The ecological legacy of Ngayu Ayu: Bridging indigenous wisdom, Islamic accountability, and sustainability - Bayu Tri Cahya; Muhammad Qoes Atieq; Jadzil Baihaqi; Nor Aishah Mohd Ali (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The Ngayu Ayu ritual represents an indigenous socio-cultural institution that embodies Islamic values of gratitude (shukr), stewardship (khalifah), and collective responsibility in managing natural resources. Beyond its cultural significance, the ritual provides insights into how local communities integrate religious values, environmental ethics, and socio-economic sustainability. This study examines the Ngayu Ayu tradition among the Sasak community in Sembalun, Lombok, to explore how Islamic values and local wisdom contribute to sustainable community development from the perspective of Islamic accountability and sustainability. Using an ethnomethodological approach, data were collected through in-depth interviews with traditional leaders, religious leaders, village elders, and community members. The findings reveal three interrelated dimensions. First, Ngayu Ayu serves as a manifestation of Islamic faith and gratitude to Allah for the blessings of nature, expressed through communal worship, buffalo sacrifice, and collective prayers that reinforce environmental stewardship and social solidarity. Second, the ritual functions as a mechanism for preserving social cohesion, strengthening mutual cooperation, and fostering collective responsibility for safeguarding natural resources. Third, the growing commercialization of the tradition through tourism creates challenges in maintaining its sacred values and balancing economic opportunities with religious and cultural integrity. From an Islamic accounting perspective, these findings demonstrate that accountability extends beyond financial reporting to encompass moral, social, and environmental responsibilities (amanah) toward Allah, society, and nature. The study contributes to the growing literature on Islamic accounting and sustainability by illustrating how indigenous religious traditions provide ethical foundations for accountability, environmental stewardship, and sustainable socio-economic development.